(untitled) (Research, Society and Development, 2022)
COVID-19 has variable clinical manifestations, ranging from an asymptomatic carrier, mild respiratory disease, pneumonia, acute respiratory distress syndrome (ARDS), multiple organ failure, and even death. Some important examples of comorbidities that can worsen the development of the disease are the components of the metabolic syndrome (MS), such as hypertension, type 2 diabetes mellitus (DM2), and obesity. The present study aimed to evaluate the susceptibility of COVID-19 cases in patients with or without criteria characterizing MS. This is an analytical cross-sectional study with a quantitative approach based on data from a sample of individuals seen at the Military Policeman’s Hospital (MPH). The results were: 43% of patients with MS were infected by SARS-CoV-2 (p < 0,05); Of all infected, 50,56% were classified by BMI with obesity, 40.90% with fasting glucose > 99 mg/dL, 43,50% with HDL-c below normal value, 39,91% with triglycerides above normal value, 41,94% in use of antihypertensives, 40,74% in use of hypoglycemic agents and 32,89% in use of hypolipemic agents. The acquired and analyzed data concluded that patients with MS have a higher risk of contracting COVID-19.